ANALISIS IMPULSE BUYING DENGAN POSITIVE EMOTION SEBAGAI VARIABEL INTERVENING (STUDI KASUS PELANGGAN TOKO ELZATTA PEKALONGAN) - Imron, Ali; Notoatmojo, M. Iqbal; Ariyanti, Rizka (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the effects of store atmosphere, hedonic shopping value, and fashion involvement on positive emotion and impulse buying, using positive emotion as an intervening variable. This research, which is being conducted at Elzatta store Pekalongan, emphasizes how important it is to create a berbelanja that is entertaining in this era of rapid advancement. This study's population consists of customers who shop at Toko Elzatta Pekalongan. The sample is collected using the purposive sampling technique. This study uses a quantitative approach with route analysis design to examine the relationship between the variables. Uji Sobel is used to assess media significance. The study's findings indicate that store atmosphere, hedonic shopping value, and fashion involvement have positive and significant effects on positive emotions. In addition, positive emotions also have a positive impact on impulsive buying. However, store atmosphere has little lasting effect on impulsive buying. This study also shows that positive emotion acts as a mediator between fashion involvement and hedonic shopping value in relation to impulse buying. The purpose of this study is to help the participants develop arousing suasana and nyaman berberanja to increase impulsive behavior.